BINATANG TOTEM PADA SENI CADAS PRASEJARAH DI SULAWESI SELATAN - Pasaribu, Yosua Adrian; Permana, R. Cecep Eka (AMERTA, 2017)
Abstract. Totemic Animals in the Prehistoric Rock Art of South Sulawesi. Prehistoric rock art motifs in South Sulawesi are hand motifs, animal motifs, boat motifs, anthropomorphic motifs, and geometric motif. Animal motifs, which include fish, turtles, birds, and mammals, are depicted in 25 of 90 prehistoric caves in the region. Research on prehistoric rock art in 2014 shows that one of the pig motifs is dated ± 35,400 years ago. Based on the diverse animal motifs depicted and the latest dating that puts the rock art area into a very old period, research on the cultural context of animal motifs on the prehistoric rock art in South Sulawesi is an interesting thing. In accordance with the research’s aim, this study is focused on animal motifs. Other motifs in the prehistoric rock art region of Sulawesi, such as anthropomorphic and geometric that allegedly have their own distinct meanings in the cultural context, require other specific investigations. This study employed a quantitative method on 86 pictures which consist of 17 animal motifs in ten caves in Maros regency, thirteen caves in Pangkep regency, and two caves in Bone regency, South Sulawesi. The application of that method to the prehistoric rock art in South Sulawesi place the cultural context in the cultural phenomenon, which is defined by experts as totemism. Keywords: Rock Art, Animal Motifs, Cultural Context, South Sulawesi, Totem Abstrak. Motif seni cadas prasejarah di Sulawesi Selatan adalah motif tangan, motif binatang, perahu, antropomorfis, dan geometris. Motif binatang yang digambarkan pada 25 dari 90 gua seni cadas prasejarah di kawasan itu, antara lain motif ikan, penyu, burung, dan mamalia. Penelitian pertanggalan seni cadas prasejarah di Sulawesi Selatan pada 2014 menunjukkan bahwa salah satu motif babi berusia ± 35.400 tahun. Berdasarkan beragamnya motif binatang yang digambarkan dan pertanggalan terbaru yang menempatkan kawasan itu ke dalam masa yang sangat tua, penelitian mengenai konteks budaya motif binatang menjadi suatu hal yang menarik. Sesuai dengan tujuan penelitian ini khusus mengkaji motif binatang. Motif lain, seperti motif antropomorfis dan geometris yang diduga kuat memiliki makna khusus dalam konteks budaya memerlukan kajian tersendiri. Penelitian ini menggunakan metode kuantitatif terhadap data berupa 86 gambar yang terdiri atas 17 motif binatang pada 10 gua di Kabupaten Maros, 13 gua di Kabupaten Pangkep, dan 2 gua di Kabupaten Bone, Sulawesi Selatan. Hasil penerapan metode penelitian tersebut menempatkan konteks budaya penggambaran motif binatang pada seni cadas prasejarah Sulawesi Selatan kedalam fenomena budaya yang didefinisikan oleh para ahli sebagai totemisme. Kata Kunci: Seni Cadas, Motif Binatang, Konteks Budaya, Sulawesi Selatan, Totem